2020
DOI: 10.1007/s13346-020-00843-z
|View full text |Cite
|
Sign up to set email alerts
|

Corticosteroids in ophthalmology: drug delivery innovations, pharmacology, clinical applications, and future perspectives

Abstract: Corticosteroids remain the mainstay of the treatment for various ocular conditions affecting the ocular surface, anterior and posterior segments of the eye due to their anti-inflammatory, anti-oedematous and anti-neovascularization properties. Prednisolone, prednisolone acetate, dexamethasone, triamcinolone acetonide, fluocinolone acetonide, and loteprednol etabonate are amongst the most widely used ophthalmic corticosteroids. Corticosteroids differ in their activity and potency in the eye due to their inheren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
91
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 155 publications
(118 citation statements)
references
References 299 publications
0
91
0
2
Order By: Relevance
“…According to Chen et al, preservative-free TAs have smaller particle size, with uniform distribution, slower dissolution, and lower free drug level in the vitreous, leading to better and longer duration of drug efficacy than preserved TA [70]. These microcrystal TA drug particles form a depot after intravitreal injection, thereby inducing controlled release and long-lasting therapeutic effects [71]. Missel et al suggested that the depot formulation decreases the dissolution rates within the vitreous Recently, a depot formulation of sunitinib malate (GB-102, GrayBug Vision, Redwood City, CA, USA), a tyrosine kinase inhibitor targeting both VEGF-A and platelet-derived growth factor (PDGF), was developed and tested in a human clinical trial.…”
Section: Microparticlesmentioning
confidence: 99%
“…According to Chen et al, preservative-free TAs have smaller particle size, with uniform distribution, slower dissolution, and lower free drug level in the vitreous, leading to better and longer duration of drug efficacy than preserved TA [70]. These microcrystal TA drug particles form a depot after intravitreal injection, thereby inducing controlled release and long-lasting therapeutic effects [71]. Missel et al suggested that the depot formulation decreases the dissolution rates within the vitreous Recently, a depot formulation of sunitinib malate (GB-102, GrayBug Vision, Redwood City, CA, USA), a tyrosine kinase inhibitor targeting both VEGF-A and platelet-derived growth factor (PDGF), was developed and tested in a human clinical trial.…”
Section: Microparticlesmentioning
confidence: 99%
“…The objective of this study was to elucidate the effect of surface properties of polyestersbased micro-and nanoparticles with different hydrophobicities on the release kinetics of the encapsulated model drug prednisolone. This corticosteroid was selected as a model drug for future studies because it was extensively used in treatments of numerous inflammatory eye diseases [4,26,40], either in the form of eye drops or ointment. The in vitro prednisolone release profiles during 720 h (Figure 3A,C) and 6 h (Figure 3B,D) clearly show the effect of both MPs and NP surface modification on the drug dissolution kinetics.…”
Section: Release Kinetics Of Prednisolonementioning
confidence: 99%
“…Nanotechnology is currently attracting attention for improving the treatment of ocular anterior and posterior segments disorders [1][2][3]. Thereby topical, intravitreal, subconjunctival, and systemic administrations appear feasible [4]. Topical treatment is the most convenient route and is most frequently used for conventional formulations in ophthalmology [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…While some of the well-known side effects of corticosteroids (cataracts, increased IOP, etc. ), were outlined in a recent review by Gaballa et al, they also outlined the potential to mitigate such effects by localized, low dose administration, and highlighted the continued interest in the ophthalmic treatment potential of these drugs [ 4 ].…”
Section: Introductionmentioning
confidence: 99%